To prove that.... plaza answer this fastly...
Attachments:
![](https://hi-static.z-dn.net/files/dba/05bb9d90bec24ae85542b5c6c42f4440.jpg)
Answers
Answered by
2
=> (cotA -cosA)/(cotA + cosA) = (cosecA-1)/. (cosecA+1)
=> (cotA -cosA)/(cotA + cosA)
=> ((cosA/sinA)-cosA) / ((cosA/sinA)-cosA)
taking cosA common from numerator nd denominator & cancelling it we get
((1/sinA)-1)/((1/sinA)+1) since 1/sinA=cosecA
therefore,
=> (cosecA-1)/(cosecA+1)
Hope it helps..
Thank You !
=> (cotA -cosA)/(cotA + cosA)
=> ((cosA/sinA)-cosA) / ((cosA/sinA)-cosA)
taking cosA common from numerator nd denominator & cancelling it we get
((1/sinA)-1)/((1/sinA)+1) since 1/sinA=cosecA
therefore,
=> (cosecA-1)/(cosecA+1)
Hope it helps..
Thank You !
THERANGER:
plzz answe my new question
Answered by
1
Here is the solution
Attachments:
![](https://hi-static.z-dn.net/files/d61/25c652bcc10181dd582bb1c5cddb6098.jpg)
Similar questions